2022
DOI: 10.1039/d1se01750k
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable strategy for spent Li-ion battery regeneration: microwave-hydrothermal relithiation complemented with anode-revived graphene to construct a LiFePO4/MWrGO cathode material

Abstract: Spent LiFePO4 (LFP) cathodes were revived through a microwave-hydrothermal relithiation process, complemented with microwave-reduced graphene oxide (MWrGO) derived from spent graphite anodes, to form a composite LFP/MWrGO cathode material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The regenerated cathode shows a cyclic retention of about 92 % at C/3 after 60 cycles. Jiang et al [61] demonstrated the successful relithiation of spent LiFePO 4 (LFP) batteries via the microwavehydrothermal process. They have developed a new cathode material by refurbishing the spent cathode and microwavereduced graphene oxide (MWrGO) anode for high electrochemical performances.…”
Section: Hydrothermal Process Of Relithiationmentioning
confidence: 99%
“…The regenerated cathode shows a cyclic retention of about 92 % at C/3 after 60 cycles. Jiang et al [61] demonstrated the successful relithiation of spent LiFePO 4 (LFP) batteries via the microwavehydrothermal process. They have developed a new cathode material by refurbishing the spent cathode and microwavereduced graphene oxide (MWrGO) anode for high electrochemical performances.…”
Section: Hydrothermal Process Of Relithiationmentioning
confidence: 99%
“…The use of mild acids coupled with microwave‐assisted heating/ultrasonication promises an environment friendly and time‐saving leaching process. [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…The use of mild acids coupled with microwave-assisted heating/ultrasonication promises an environment friendly and timesaving leaching process. [16][17][18] Most battery recycling papers focus on strategies to recover elements from the parent compound. [19][20][21][22][23] For instance, Zou et al [24] employed a technology to dispose of the mixed raw cathode materials and obtained regenerated cathode materials as products with good electric performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to insufficient contact between the Li source and the spent LFP, the structure of the regenerated LFP is likely to be heterogeneous. [13,14] Hydrothermal treatment can overcome the shortcomings of the solid-state calcination method. Chen et al repaired spent LFP by hydrothermal methods with citric acid as a reducing agent followed by an annealing process.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Yet, the problems regarding toxicity and the cost of reducing agents remain to be solved. [14,17,18] Another issue associated with the regenerated LFP is poor cycling stability, [13,[19][20][21][22] which hinders its practical applications. This problem occurs because LFP can provide only a 1D Li + transport channel during cycling (sluggish Li + diffusion capability), and the extracted Li + cannot return to their original Li + sites at a high current density, which induces the formation of FePO 4 (FP) phase during cycling, leaving a large number of Li + vacancies (Li V ) in the LFP.…”
Section: Introductionmentioning
confidence: 99%